Iron oxide looping for natural gas conversion in a countercurrent moving bed reactor. (1st November 2015) - Zeng, Liang; Tong, Andrew; Kathe, Mandar; Bayham, Samuel; Fan, Liang-Shih
Highlights: Countercurrent moving bed studied for chemical looping conversion of natural gas. Thermodynamic criteria developed using Ellingham diagram and ASPEN Plus Gibbs model. Critical Fe2 O3 /CH4 molar ratio is determined for complete CH4 conversion. The advantages of the proposed moving bed reactor design are proofed with both the modeling and bench scale experimental results. Abstract: Chemical looping technologies have the potential to reduce the natural-gas conversion cost in a carbon-constrained scenario. Given the increasing importance of natural gas to global energy supply, this work investigates the application of an iron oxide based chemical looping technology for natural gas conversion. A thermodynamic criterion for selecting iron oxide based oxygen carrier material and designing the reaction system is developed using an adapted Ellingham diagram. Equilibrium modeling for detailed thermodynamic analysis is conducted for verifying the Ellingham diagram analysis. The thermodynamic equilibrium model also establishes a system baseline performance, and experimental proof of concept bench-scale demonstration is investigated. The bench-scale testing is used to characterize the effect of parameters like solids to gas ratio and temperature of the reactor on system performance. An optimal set of operating conditions is identified for further testing on a larger scale.